Postnatal depression: An understanding of Malaysian perspectives - Binti Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2014)
Background: Postpartum depression (PND) is considered as a significant health problem and gained special attention due to women’s vulnerability during childbearing years, highly associated with suicide and its negative impacts on women, child, family and society. Despite these concerns, PND has still remains underdiagnosed and undertreated in the clinical practice. Previous studies suggest that sociocultural context of motherhood have a link with PND and that treatment of PND should be culturally appropriate, yet there was no research on the Malaysian women’s experience of PND have been published up to this date. Objectives: The aims of this study are to: i) explore postnatal women’s perceptions of PND in Malaysia, ii) understand the experience of PND among postnatal women in Malaysia, iii) explore the knowledge and perception of Malaysian healthcare professionals on PND and helpful strategies for its management and iv) explore potential interventions for women with PND in Malaysia. Method: This study will employ an exploratory qualitative design. The critical realism will be considered as the philosophical framework underpinning the study. The planned population for this study are 45 postnatal women with different Malaysian cultural backgrounds who attend for postnatal care or child immunization at five selected Maternal and Child Health (MCH) Clinics in Kuala Lumpur and Putrajaya, Malaysia; and 15 health care professionals involved with postnatal care in the selected clinics and Psychiatric Ward, Hospital Kuala Lumpur. The women will be screened for postnatal depressive symptoms using The Patient Health Questionnaire-2 (PHQ-2). Those who score three or more in PHQ-2 will be invited for the interview session. The face to face semi structured interviews will be used to explore the women’s perspectives of PND and understand the perceptions of Malaysian healthcare professionals on PND. The contact with Malaysian Medical Research Ethics Committee (MREC) and Malaysian National Institute of Health Research (NIHR) will be initiated through the registration with the Malaysian National Medical Research Register (NMRR) upon getting ethical approval from School Research Ethics Committee (SREC) in the School of Nursing, Midwifery and Health, University of Stirling. Data collection and data analysis will be conducted concurrently. Data will be analysed using thematic analysis. Nvivo, a software package will be used to develop coding on each transcript. Conclusion: This study will add on the theoretical concepts of PND and its relation to cultural background through understanding and exploration of PND experience from Malaysian perspectives. It will also encourage further high quality work to provide effective, relevant and culturally sensitive intervention for PND. The findings of this study will be the foundation of developing preventative intervention for PND in Malaysia.